Transfer of Teachers and Learners’ Performance in Kabarole District. - Bychance, Allan (Kabale University, 2024)
This study investigated the correlation between teacher transfers and learners’ academic performance in government-aided primary schools in Kabarole District. The specific objectives were to determine the relationship between voluntary teacher transfers and learners' academic performance, to assess the impact of routine teacher transfers on academic performance, and to examine the effect of forced teacher transfers on learners' academic performance in government-aided primary schools within the district. A cross-sectional research design was employed, integrating both quantitative and qualitative approaches. From a target population of 369 respondents, a sample size of 248 was selected using purposive and simple random sampling techniques. Of the sample, 195 respondents participated fully, yielding a response rate of 78.6%. The study found a significant positive relationship between voluntary transfers and learners' performance (r = 0.640, p = 0.000). Additionally, there was a significant positive relationship between routine transfers and learners' performance (r = -0.816, p = 0.000), as well as between forced transfers and learners' performance (r = -0.814, p = 0.000). The study concluded that voluntary, routine, and forced transfers enhance teacher innovativeness and performance. Recommendations included promoting voluntary transfers to foster teacher creativity and improve performance, maintaining routine transfers as a beneficial policy for performance, and justifying forced transfers for underperforming teachers to improve learner outcomes. The Ministry of Education and Sports (MOES) was encouraged to implement these strategies to optimize academic performance.